2019
DOI: 10.1038/s41467-019-11467-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional aromaticity in an antiaromatic cyclophane

Abstract: Understanding of interactions among molecules is essential to elucidate the binding of pharmaceuticals on receptors, the mechanism of protein folding and self-assembling of organic molecules. While interactions between two aromatic molecules have been examined extensively, little is known about the interactions between two antiaromatic molecules. Theoretical investigations have predicted that antiaromatic molecules should be stabilized when they stack with each other by attractive intermolecular interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 37 publications
2
86
0
1
Order By: Relevance
“…The comparatively high stability of Ni(II) norcorrole makes it an ideal molecule to study stacking interactions between antiaromatic π ‐conjugated systems and the ensuing emergence of three‐dimensional aromaticity. Initially, stacking of flexibly linked Ni(II) norcorrole complexes was investigated, [37] followed by a more recent report of a rigid cyclophane composed of two Ni(II) norcorrole units and two bithiophene linkers [38] . These studies highlighted the importance of through‐space currents connecting the two macrocycles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparatively high stability of Ni(II) norcorrole makes it an ideal molecule to study stacking interactions between antiaromatic π ‐conjugated systems and the ensuing emergence of three‐dimensional aromaticity. Initially, stacking of flexibly linked Ni(II) norcorrole complexes was investigated, [37] followed by a more recent report of a rigid cyclophane composed of two Ni(II) norcorrole units and two bithiophene linkers [38] . These studies highlighted the importance of through‐space currents connecting the two macrocycles.…”
Section: Resultsmentioning
confidence: 99%
“…Within this work, we study the Ni(II) norcorrole complex reported in Ref. 35 but with removed bithiophene linkers, as shown in Fig. 7 (b).…”
Section: Norcorrole Dimer -Through-space Aromaticitymentioning
confidence: 99%
See 1 more Smart Citation
“…NICS values can be visualised after computing them on a grid around the molecule of interest [45][46][47][48] and several recent applications present 1D scans, 2D contour plots or even 3D isosurfaces of the isotropic NICS values, e.g. to visualise local aromatic and antiaromatic parts of larger molecules, 6,22,35,49 to represent Clar sextets in condensed hydrocarbons, 50 or to study interactions in excimers. 51 These visualisations are almost exclusively based on isotropic NICS values.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] It was further theoretically extended to open-shell systems by Solà et al 41 In addition, close stacking between antiaromatic molecules could lead to enhanced aromaticity. [42][43][44] All these studies demonstrate that π-/σ-conjugated molecules or clusters always have the tendency to reach the lowest-energy state (aromatic) through electron delocalization. Surprisingly, the investigated 3D aromatic systems cover very little about the fully π-conjugated molecular cages or polyhedrons, although 2D π-aromaticity was widely studied.…”
mentioning
confidence: 99%